Chemical composition of selected winter green pea (Pisum sativum L.) genotypes - Červenski Janko; Danojević Dario; Savić Aleksandra (Journal of the Serbian Chemical Society, 2017)
Breeding and selection of winter pea for seed quality is a serious challenge to every breeder. The result of breeding mainly depends on good knowledge of the genetic material. Chemical and technological analysis is necessary for an accurate determination of the following traits of technologically mature seed of the winter pea collection: protein content, total nitrogen content, total sugars content, starch content, fatty oil content, cellulose content, and ash content (g (100 g)-1). The protein content in the tested lines of pea was in the range 22.86–28.04 g (100 g)-1, the total nitrogen content 3.66–4.49 g (100 g)-1, total sugars content 10.30–14.67 g (100 g)-1, starch content 39.44–46.23 g (100 g)-1, fatty oil content 1.48–1.89 g (100 g)-1, cellulose content 8.79–10.28 g (100 g)-1 and ash content 3.08–3.67 g (100 g)-1. PCA analysis was used to identify the three components that collectively explained 81.59 % of the total variation. The first component was mainly defined by the ash and the total nitrogen, protein and cellulose contents. The second one, independent from the first one, was mainly correlated to the fatty oil and starch contents, while the third was defined by the content of total sugars. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR 31030: Development of vegetable cultivars and hybrids intended for outdoor and indoor production]